Belize s agriculture on the map - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Belize Farms Register Ministry of Agriculture, Fisheries and Cooperatives 2nd Floor, West Block Building, Belmopan, Belize Fax: + 501 8 224 09 Email: mafpaeu@btl.net